The Influence of Entrepreneurial Supply Chain on Marketing: An Exploratory Case Study of General Company for Batteries Manufacturing - Maha Arif Breesam; Khaldia M.Atta; Mudher Salih Mahdi (International Journal of Supply Chain Management, 2019)
The current research examines the relationship of the Entrepreneurial supply chain dimensions (proactive approach, innovation, risk management and customer focus) with the supply chain strategies (undifferentiated marketing strategy, concentrated marketing strategy and differentiated marketing strategy). The focus of this investigation is to explore the role of adoption of entrepreneurial supply chains in the identification and selection of the appropriate strategy for the target market in the context of general company foe batteries manufacturing. The essence of entrepreneurial supply chains is its ability to facilitate alignment of all participants in the chain, eliminating moral hazard and opportunism risks. The importance of the research is derived from the significance of the matter. A companyâ€™s success or failure depends on the appropriate target market strategy. The questionnaire techniques was used as a data collection tool designed on the basis theoretical conceptualization of the model. Â The research found a significant role of Entrepreneurial supply chain and its underlying dimensions on the selection of target market strategies. Furthermore, the relationship of the Entrepreneurial supply chain differentiated market strategy has found stronger among all. Hence company's management should adopt differentiated marketing strategy as the most appropriate in achieving its objectives